Synthesis of community-based watershed rehabilitation and management activities in Jordan and Afghanistan – towards out-scaling - Strohmeier, S. (2021)
ICARDA, in affiliation with the CGIAR Research Program on Water Land and Ecosystems (WLE), has undertaken various community-based watershed activities with its local country partners. ICARDA’s portfolio includes the ongoing watershed rehabilitation and management activities in Jordan and past bilateral projects conducted in, e.g., Afghanistan. The agropastoral Rehabilitation approach conducted in Jordan has considerable potential for out-scaling and is under evaluation through an ongoing WLE initiative targeting the marginal drylands in south-eastern Ethiopia. Pursuing an ex-ante out-scaling approach (through modeling) builds on well-selected socioecological criteria and limitations and considers the experiences and lessons learned from previous project activities.